HUMOUR AS A COUNTER ISLAMIST DISCOURSE - Khalimatu Nisa (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2023)
This article addresses counter-Islamist discourses by NU Garis Lucu (NU’s Funny Brigade) through its social media accounts. Instead of a clear-cut theological debates, NU Garis Lucu offers humour as method to counter attack Islamist’s arguments through its social-media activism. Using a discourse analysis approach, this article examines tweets of the NU Garis Lucu’s during the course of 2015-2020. It further reveals the account strategies to counter attack Islamist’s discourse which include questioning the legitimacy of the religious authority of Islamist groups, promoting religious moderation, supporting democracy as an ideal political system, promoting ‘smiling’ Islam, and putting to an end religious polarization.